ANALISIS TINGKAT KUALITAS PELAYANAN DAN PARTISIPASI ANGGOTA KOPERASI PADA KOPERASI WANITA PESONA MARTA (KOPWAPETA) KOTA PEKANBARU - Muhammad Bintang Nagara; Suarman Suarman; Hendripides Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this study was to find out how the level of service quality and participation of members in the Koperasi Wanita Pesona Marta Pekanbaru. The population in this study was 149 people. Sampling in this study used simple random sampling technique used the Slovin formula amounted to 60 people. Data collection using questionnaires. Data analysis using descriptive quantitative method. The results showed that the level of service quality of the Pesona Marta Pekanbaru Women's Cooperative was in the low category with a percentage of 61.66%. And the level of participation of members of the Koperasi Wanita Pesona Marta Pekanbaru is in the 46.67% category.Key Words: Service Quality, Member’s Participation